2006
DOI: 10.1021/cm052662z
|View full text |Cite
|
Sign up to set email alerts
|

Coloration and Decoloration of Tungsten Phosphate Glasses by Heat Treatments at the Temperature Far below Tg under a Controlled Ambient

Abstract: Reversible coloration−decoloration of tungsten phosphate glasses was observed by heat treatments at temperatures between 300 and 500 °C which were far below the T g (570 °C) under the ambient with controlled partial pressure of hydrogen and/or water. The color center responsible for the coloration was found to be an electron-trapped W5+. The assignment was done by detecting an anisotropic ESR singlet of g = 1.7 and broad optical absorption bands extending from the visible to the near-infrared region. The charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…content dependence of the change, DP H2 , in the hydrogen partial pressure in room-2 measured by exposing glass specimens to water vapor at 500°C. The inset shows the time dependence of P H2 in room-2 for a specimen of 30Na 2 …”
Section: Catalytic Reaction Of 30namentioning
confidence: 99%
See 1 more Smart Citation
“…content dependence of the change, DP H2 , in the hydrogen partial pressure in room-2 measured by exposing glass specimens to water vapor at 500°C. The inset shows the time dependence of P H2 in room-2 for a specimen of 30Na 2 …”
Section: Catalytic Reaction Of 30namentioning
confidence: 99%
“…Recently, it was reported that some phosphate glasses containing tungsten oxide decompose water vapor and absorb hydrogen [2,3]. Spectrometric studies on these glasses showed that the glasses had absorption bands in the IR and visible (600-650 nm) regions, which were assigned to the vibration mode of O-H and the absorption by W 5+ ion, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For a value of x ≤ 0.33, glasses are transparent [24], which can be used for modeling typical glass applications such as sensors for the investigation of structural aspects of the amorphous materials [29,13]. Tawarayama et al reported that during heat treatment, the 30Na 2 O-10BaO-30P 2 O 5 -20Nb 2 O 5 -10WO 3 glass is permeable to hydrogen, and as monoatomic hydrogen passes through the glass, it is reducing tungsten ions from W 6+ to W 5+ [30,31]. They proposed that the fast coloration requires fast diffusion of electrons and protons introduced into the glass.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten phosphate glasses react with hydrogen and water vapor at the ambient temperatures below the glass transition temperature (T g ) and W 6+ ions in the glasses are reduced to W 5+ [7,8]. The reduced tungsten ions, W 5+ , show strong intraionic and intervalence optical absorptions in the visible to near infrared region and the color of the glass changes to dark blue.…”
Section: Introductionmentioning
confidence: 99%